Dual Structure‐Material Design of Separators toward Dendrite‐Free Lithium Metal Anodes. Issue 20 (15th September 2022) - Su, Zhengkang; Wang, Biao; Li, Linyan; Yang, Guang; Yu, Aishui; Li, Guang; Zhang, Jingjing
Abstract: The practical applications of lithium metal anodes have been severely hindered by the Li dendrite issue. Herein, a dual structure‐material design strategy was developed to fabricate a new type of separator using interconnected hollow porous polyacrylonitrile (PAN) nanofibers (HPPANF), which delivered controllable and dendrite‐free Li depositions. The interconnected mesopores on HPPANF bridged the hollow interiors with the outside voids among the fibers, enabling outstanding electrolyte uptake capabilities for high ion conductivity, and nano‐level wetted electrolyte/anode interface for uniform Li plating/stripping. In parallel, the HPPANF separator enriched with polar groups acted as an exceptional polymer‐based solid‐state electrolyte, providing 3D ion channels for the transport of Li ions. Benefiting from the dual structure‐material design, the HPPANF separator induced uniform Li ion flux for dendrite‐free Li depositions, which caused enhanced cycling stability (1300 h, 3 mA cm −2 ). This work demonstrates a new method to stabilize Li metal anodes through rational separator design. Abstract : PAN separator : A dual structure‐material design strategy to fabricate a separator based on hollow porous polyacrylonitrile (PAN) nanofibers is proposed. The interconnected 3D pores enable outstanding electrolyte uptake capabilities for high ion conductivity. PAN with abundant polar groups acts as a polymer‐based solid‐state electrolyte and provides 3D ion transport routes, collectively inducing uniform Li ion flux for dendrite‐free Li depositions.